2015
DOI: 10.5194/bg-12-5075-2015
|View full text |Cite
|
Sign up to set email alerts
|

Effects of fluctuating hypoxia on benthic oxygen consumption in the Black Sea (Crimean shelf)

Abstract: Abstract. The outer western Crimean shelf of the Black Sea is a natural laboratory to investigate effects of stable oxic versus varying hypoxic conditions on seafloor biogeochemical processes and benthic community structure. Bottom-water oxygen concentrations ranged from normoxic (175 μmol O2 L−1) and hypoxic (< 63 μmol O2 L−1) or even anoxic/sulfidic conditions within a few kilometers' distance. Variations in oxygen concentrations between 160 and 10 μmol L−1 even occurred within hours close to the chemocli… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 82 publications
(97 reference statements)
0
11
0
2
Order By: Relevance
“…Higher amounts of some metals in sediments from Sinop Peninsula reflect that the sediments act as a settle and source for these metals. Sediment accumulation rates were around 1 ± 0.5 mm year −1 for the upper 10 cm of the oxic-hypoxic and the hypoxic-sulfidic zone in the Black Sea (Lichtschlag et al, 2015) and sediments are of fine-grain muddy composition with a brownish grayish fluff layer on top about 0.5 cm (Jessen et al, 2017). In general results showed that decreasing of the metal levels with increasing depth of the sediment.…”
Section: Resultsmentioning
confidence: 85%
“…Higher amounts of some metals in sediments from Sinop Peninsula reflect that the sediments act as a settle and source for these metals. Sediment accumulation rates were around 1 ± 0.5 mm year −1 for the upper 10 cm of the oxic-hypoxic and the hypoxic-sulfidic zone in the Black Sea (Lichtschlag et al, 2015) and sediments are of fine-grain muddy composition with a brownish grayish fluff layer on top about 0.5 cm (Jessen et al, 2017). In general results showed that decreasing of the metal levels with increasing depth of the sediment.…”
Section: Resultsmentioning
confidence: 85%
“…Because these relatively large organisms are vulnerable to physical disturbance from human activities such as bottom trawling ( Clark et al, 2016 ), a decrease in their density and/or diversity would likely result in a loss in ecosystem function. Evaluating the magnitude of this loss, which is likely to be greatest in relatively high productivity upper continental slope habitats where large benthic fauna are most abundant ( Leduc, Pilditch & Nodder, 2016 ), may be aided by the application of functional trait assessment approach ( Bremner, Rogers & Frid, 2003 ) and the use of in situ O 2 consumption measurement method capable of integrating larger and therefore more representative areas of the seabed, such as in situ benthic chamber incubations ( Lichtschlag et al, 2015 ) or the eddy correlation flux method ( Berg et al, 2009 ).…”
Section: Resultsmentioning
confidence: 99%
“…По градиенту глубины в Чёрном море выделены четыре зоны в зависимости от концентрации кислорода в придонных водах (Lichtschlag et al 2015): кислородная, глубины <130м (> 63 μmol L -1 ), кислородная/гипоксическая, глубины 130-142 м (> 63 to > 0 μmol L -1 ), гипоксическая/бескислородная, глубины 142-167 m (63-0 μmol L -1 ) и бескислородная/ сульфидная, глубины > 167м (в бескислородной воде присутствует сероводород).…”
Section: глава 4 распределение мягкораковинных фораминифер черного моря по градиенту глубины от нормоксии до постоянной гипоксии и аноксиunclassified
“…Условия среды для мейобентосных организмов в зависимости от концентрации кислорода в воде придонных слоев вдоль пограничной зоны на внешнем западном крымском шельфе и в районе Стамбульского пролива Чёрного моря варьировали от нормоксии (175 мкмоль O 2 L -1) к гипоксии (менее <63 мкмоль O 2 L -1) и аноксии с сероводородом на протяжении нескольких километров (Holtappels et al, 2011;Lichtschlag et al, 2015).…”
Section: глава 4 распределение мягкораковинных фораминифер черного моря по градиенту глубины от нормоксии до постоянной гипоксии и аноксиunclassified